Herskende religion i den kristelige stat Ideer om religion og stat og deres betydning for norsk religionspolitikk i 1840-årene - Aschim, Per Kristian (Scandinavian University Press (Universitetsforlaget), 2022)
This book examines legal and state theoretical ideas on the relationship between religion and state, and its significance for the politics of religion in Norway in the 19th century. The main sources are Norwegian and Danish literature on legal and state theory, including literature that interprets the Constitution's provisions on religion. The analysis shows that constitutional and state philosophical theories on religion and state had significant impact on the development of the politics of religion in Norway.